Placing Knowledge as Resurgence - Lee, Damien (InTensions, 2012)
This article discusses Anishinabek (Ojibwa) knowledge as a manifestation of human connection and re-connection to place. Colonialism in Canada is predicated on taking land from Indigenous peoples, or taking Indigenous peoples away from their land; such removals have had a negative impact on some Indigenous knowledges. However, rather than accepting that such knowledge is gone forever when individual people are silenced, this article posits that Anishinabek knowledge is still in the land, and that it can resurge through our relationship with place. The article centres on a narrative about reconnecting with knowledge told by my grandmother, Geraldine MacLaurin-ba, and goes on to (re)envision how such knowledge constitutes a resurgence of Anishinabek self-determination.